STUDY OF SOME MICROBIAL PROPERTIES FOR MICROLAMINATE OF ALGINATE AND CINNAMON IN LBL TECHNIQUE USED IN THE CHEDDAR CHEESE COATING - Jawad , Azhar; Khairi, Shaymaa R. (Diyala Agricultural Sciences Journal, 2020)
This study was carried out to evaluate the preparation of five-layer microlaminates that were introduced by Layer By Layer (LBL) technique by the use of two solutions, namely, the sodium alginate, and the other antimicrobial agent is the cinnamon extract. The halo diameter was estimated on a petri dish containing the positive bacteria Staphylococcus aureus and Bacillus subtilis or negative gram bacteria E. coli and Pseudomonas aeuroginosa, Enterococcus ssp. Aspergillus niger and Fusarium were used to estimate the effectiveness of antimicrobial extracts. Results showed that 0.2% concentration of cinnamon extract showed inhibitory activity against these microorganisms. The scanning electron microscope was used to detect the thickness of prepared microlaminates . The thickness of the total alginate and cinnamon microlaminate was 22.47 micron , The Zeta Potential voltage of the alginate solution reached -28.49 mV at pH = 7 and the cinnamon extract was 28.69 mV, The WVP water permeability values for the micrlayered PET film without any addition to the charged PET (treatment 1) were 29.091 g.m2 /24h) and for the microlayered PET-charged for sodium alginate and Cinnamon extract (treatment 2), OTR was obtained for the micrlayered with no addition of the charged PET (treatment 1), 14.78 ml / m2 .day), and for the PETcharged, covered with sodium alginate and cinnamon extract (treatment 2) 17.95 ml /m2 .day.Three treatments were made of Monterey cheese, the first treatment was covered with the paraffin wax as control M1, the second was covered with gelatin (M2) and the third was coated with a micrlayered film consisting of the sodium alginate and the cinnamonextract (M3). The results indicated that the presence of the cinnamon extract was determined by the microbiological growth of the treatment (M3), which made it superior to the comparison treatments.